Identificação de alguns constituintes químicos de Indigofera hirsuta Linn. (Fabaceae) por CLAE-IES-EM (TOF) e avaliação da atividade antirradicalar - Moura, Adriana Candido da Silva [UNESP]; Vilega, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP] (Sociedade Brasileira de Química, 2011)
A rapid analytical approach, suitable to characterize the compounds present in the aqueous and methanol extracts prepared from the aerial parts of Indigofera hirsute, was developed. The method based on high-performance liquid chromatography coupled to mass spectrometry, electrospray positive ionization and detection by time of flight (HPLC-ESI-MS-TOF) identified, tryptophan, uracil, rutin, kaempferol-3-O-β-D-glucopyranoside, gallic acid and methyl gallate. The antiradical activity of this extract was evaluated using DPPH assay, with gallic acid as antiradical pattern. The study revealed the antiradical activity of methyl galatte (EC50 = 5 ± 0.3 µg mL-1) galic acid (EC50 = 5 ± 0.2 µg mL-1) and rutin (EC50 = 21.6 ± 0.6 µg m L-1), isolated from methanol extract (EC50 = 67.7 ± 0.9 µg mL-1), which showed strong antiradical activity.
Identification of some chemical constituents of Indigofera hirsuta Linn. (Fabaceae) by HPLC-ESI-MS (TOF) and evaluation of the antiradical activity
Keywords: Indigofera hirsuta; mass spectrometry; antiradical activity